Cellular responses of oil palm genotypes during somatic embryogenesis involve participation of procambial cells, DNA demethylation, and auxin accumulation - De Araújo Silva-Cardoso, I. M.; Gomes, A. C. M. M.; Scherwinski-Pereira, J. E.
To assess the potential of different genotypes of Brazilian oil palm (Elaeis guineensis Jacq.)to somatic embryogenesis and somatic embryo proliferation, mature zygotic embryos of nine commercial genotypes of E. guineensis (BRSC2001, BRSC2328, BRSC2301, BRSC3701, BRSCM1115, BRSC7201, BRSC2528, BRSC2501, and BRSCN1637)were used. Explants were incubated on Murashige and Skoog (MS)supplemented with 450 ?M picloram, 3.0 percent sucrose, 500 mg l?1 glutamine, and 2.5 g l?1 activated charcoal, and gelled with 2.5 g l?1 Phytagel. After induction, for differentiation and maturation, the embryogenic calli (ECs)were transferred into fresh medium supplemented with 0.6 ?M naphthaleneacetic acid (NAA)and 12.30 ?M 2-isopentenyladenine (2iP)or 40 ?M picloram in combination with 0.3 g l?1 activated charcoal, and 500 mg l?1 glutamine. Somatic embryos were converted into plants on MS medium with macro- and micro-nutrients at half strength, 2 percent sucrose, and 2.5 g l?1 activated charcoal, and gelled with 2.5 g l?1 Phytagel. In general, zygotic embryos swelled after 14 days. Primary calli, which were observed in all the genotypes after 45-60 days of culture, eventually progressed to ECs at 90 days. At this time, scanning electron microscopy (SEM)analysis showed cellular differences between compact and friable calli. After 150 days in the induction phase, the ECs with proembryos that were transferred to the medium for differentiation and maturation, differentiated asynchronically into somatic embryos at globular and torpedo stages. The results showed that BRSC2328 and BRSCM1115 had the highest potential for EC formation (90-100 percent)and somatic embryo differentiation (40.7 and 52.5 somatic embryos per callus, respectively)when compared to other genotypes. After approximately 90 days of culture on MS basal medium without growth regulators, protrusion of the leaf primordia was observed, characterizing the onset of germination of the somatic embryos into plants.
Keywords: PALM TREE; CALLUS; GENOTYPE DEPENDENCY; STEM CELL VASCULAR; EPIGENETIC; IMMUNOFLUORESCENCE